Spillover-effects, crowding-in and the contributions of FDI to growth in China: A review of the literature - Markus Taube (Universität Duisburg-Essen, Forschungsinstitut für Wirtschaftliche Entwicklungen im Pazifikraum (FIP), 2005)
The paper presents a review of theoretical concepts and empirical findings on the issue of FDI-induced spillover and crowding-effects in the Chinese economy. Against the background of the peculiar characteristics of China's FDI-inflows the paper discusses various research agendas and results. It finds mostly inconclusive evidence, which is understood to result from an insufficient analytical differentiation of FDI and host economy actors. On the 'supply'-side of FDI it seems to be necessary to include the parameter of 'cultural affinity' in the analysis and differentiate between Overseas Chinese and non-Chinese investors (with the latter probably featuring a greater potential for positive externalities). On the 'demand'-side it seems to be adequate to differentiate between the state and collective / private domestic sector and analyze their respective incentives to actively explore potential spillover effects and actually appropriate new technologies introduced by foreign investors. It seems as if the harder the budget constraints and the more competitive the environment, the greater the realized spillover effects. It becomes obvious that most existing studies are working with data that does not reflect the dynamic developments of the recent ten years.
Keywords: 330; Foreign direct investment; spillover-effects; crowding-in; Chinese economy; Direktinvestition; Ausländisch; Spillover-Effekt; Crowding out; Wirtschaftswachstum; Regionale Disparität; Branche; China